Impact of metabolic syndrome on the long-term prognosis of patients with hepatitis B virus-related hepatocellular carcinoma after hepatectomy - Zhang, Kang-Jun; Ye, Tai-Wei; Lu, Wen-Feng; Xu, Fei-Qi; Xie, Ya-Ming; Wang, Dong-Dong; Xiao, Zun-Qiang; Liu, Si-Yu; Yao, Wei-Feng; Cheng, Jian; Shen, Guo-Liang; Liu, Jun-Wei; et al. (Frontiers in Oncology, 2022)
Background & aims The long-term prognosis of patients with metabolic syndrome (MS) and hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) after radical hepatectomy remains unclear. The purpose of this study was to elucidate the effect of MS on long-term survival for patients with HBV-related HCC after hepatectomy. Methods Patients with HBV-HCC after hepatectomy were included. Patients were stratified into MS-HBV-HCC and HBV-HCC groups. Clinical features and surgical outcomes were compared between the two groups, and COX regression analysis was used to determine independent risk factors associated with overall survival (OS) and recurrence-free survival (RFS). Result 389 patients (MS-HBV-HCC group: n=50, HBV-HCC group: n=339) were enrolled for further analysis. Baseline characteristics showed that patients with MS-HBV-HCC were associated with a high rate of elderly patients, ASA score, and co-morbid illness, but a lower rate of anatomy hepatectomy. There were no significant differences in perioperative complications. After excluding patients who relapsed or died within 90 days after surgery, multivariate Cox regression analysis showed MS was an independent risk factor of OS (HR 1.68, 95% CI 1.05-2.70, P = 0.032) and RFS (HR 1.78, 95% CI 1.24-2.57, P = 0.002). Conclusion MS is an independent risk factor for poor OS and RFS in HBV-infected HCC patients after radical hepatectomy. This suggests that we need to strengthen postoperative follow-up of the relevant population and encourage patients to develop a healthy lifestyle.